Meixner-módszer és színészképzés - Kerkay Rita (Symbolon)
Meixner Method and Actor Training The basic principles of Ildikó Meixner’s dyslexia prevention and re-education method can be discovered in the practices of actor training at the University of Theatre and Film Arts. The principle of gradualism, building a triple association, preventing the development of Ranschburg’s homogenous inhibition, avoiding the rigidity of thinking, and improving spatial orientation are some of Meixner’s practices that prove useful in actor training.